(untitled) (Research, Society and Development, 2022)
The pharmaceutical care or pharmaceutical assistance is an ensemble of actions accomplished by the pharmaceutical professional, aimed to the promotion, protection and recovery of health. In this context, the mission of those professionals in pharmaceutical care permeates the activities discussed in the concept of pharmaceutical care, allowing continuous monitoring in relation to the therapeutic optimization of medicines. The objective of this research is to describe an experience report and evaluate the pharmacist’s challenges to apply pharmaceutical care and attention in a pharmacy in the city of Porto Alegre-RS from September to November 2021. In the results presented through the Analysis by Bardin (2016), it is evident that the pharmaceutical professional is constrained by the work team and lack of social recognition to develop the cycle of pharmaceutical care and attention, as well as to correctly dispense the medication. It is concluded that, for the pharmaceutical professional in pharmacies and drugstores, all this is still a challenge to be pursued by research and by the training of new professionals in educational institutions. With this, the active professional must keep updated about the legislation in force for these establishments.